APPLICATION OF CONTEXTUAL TEACHING AND LEARNING MODELS TO IMPROVE AQIDAH AKHLAK LEARNING OUTCOMES - Arni, Arni; Askar, Askar; Muh. Amin, Sagir; Kahar, M. Iksan (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2024)
This study investigate the Application of Contextual Teaching and Learning Models to Improve Aqidah Akhlak Learning Outcomes in State Islamic Senior High School in Morowali Regency. This study used a case study qualitative method. Data were gathered through direct observation, in-depth interview, and written document analysis. In-depth interview involving the school principal, religious teachers, and students. This study found that implementation of the Contextual Teaching and Learning (CTL) model in the Aqidah Akhlak subject at MAN Morowali facilitates students in comprehending and actively engaging in the learning process. This approach emphasizes student-centered learning, where students independently seek and discover the learning material. It creates meaningful learning experiences by linking the content to real-life contexts within social and cultural environments. Teachers play a pivotal role in encouraging active student participation, enabling them to identify and apply knowledge.